Permanent changes in the wage structure and the East German fertility crisis: conference paper - Arntz, Melanie; Gathmann, Christina (Jahrestagung des Vereins für Socialpolitik 2014, 2014)
After the fall of the Berlin wall, the total fertility rate in East Germany tumbled from 1.7 (1989) to a stunning 0.7 children per woman (1994). While this fact is well-documented, little is still known about the crisis underlying causes. We propose a new explanation: permanent shifts in the East German wage structure that are plausibly exogenous from the individual s perspective. Economic transition dramatically increased the returns to human capital in East Germany. Economic theory suggests that rising returns to experience and education favor career investment and the postponement of births. Our results suggest that women postpone fertility when the wage penalty for time off work in the current period are high; and the postponement is much stronger for high-skilled women. Overall, our estimates can account for a substantial fraction of the observed fertility decline and demonstrate that incentives in the labor market have a strong influence on fertility decisions.
Keywords: Graue Literatur; Konferenzschrift